Picture Description Using Power Point to Improve Speaking - Ogoño Caraguay, Martha Olivia (2022)
Nowadays, it is motivating and engaging the learning through pictures. They can also be used as a mean to check student’s knowledge, in the summative and formative assessment. Teaching English through pictures has some benefits since the language performance increases as well as the learners’ attitude. Bowen (1982, as cited in Nguyen et al., 2015, p. 1) stated that “learning is a complex process and visual aids are a great help in stimulating the learning of a foreign language.” Moreover, Wright (1989) claimed the resources must include pictures. After all, verbal language is only a part of the way we usually get meaning from contexts. Phuong (2018) said “the use of pictures has positive impacts not only on learners’ language performance but also learners’ attitude towards language learning.” (p. 33). Working with pictures allow the students to be engaged in the development of the activities, becoming these activities that the teacher plan are incredibly fruitful with the use of visuals. According to Education First (2020), Ecuador is in the 93rd place out of 100 countries, which means very low in Latin America. Based on my experience as an English teacher, students are afraid of speaking in English due to the lack of vocabulary they have. This makes them feel less confident to interact in class. The Curriculum for First Baccalaureate (Subnivel Bachillerato; Ministerio de Educación, 2016) contains the mandatory skills with the indicators for performance. One of the indicators establishes learners can exhibit an ability to discuss culture, the students should be able to analyze cultural products and referents from Ecuador, communicate effectively using a variety of media including Information and Communication Technology ICT, and apply self-correcting and self-monitoring strategies when needed. These indicators have two purposes: build up the national identity in search of a peaceful world and value the multi-cultural background. In addition, the students will respect the identity of other people and individuals.